A single-step three-dimensional human skeletal muscle model for enhanced translational research - Sergio Perez-Diaz; Jaime Granado Leon; Susana López-Ortiz; Mirko Mandić; Mikael Altun; Håkan Rundqvist; Thomas Gustafsson; Rodrigo Fernandez-Gonzalo (Results in Engineering)
Three-dimensional (3D) skeletal muscle models have attracted considerable attention due to their ability to reflect the complexity of skeletal muscle structure and mimic a wide range of physiological processes in vitro. However, 3D cultures are usually associated with a higher experimental complexity and cost. To overcome these limitations, we aimed to develop a serum-free 3D model of human skeletal muscle using skeletal muscle progenitor cells from human donors in a single step. After 10 days in serum-free myogenic differentiation medium, the 3D model showed greater Myosin heavy chain 1 (MyH1) expression compared to 0 and 5 days of differentiation and to classical 2D models. The 3D model responded to treatment with the atrophic agent myostatin with a reduction in MyH1 content. We also tested the regenerative capacity of the 3D model. MyH1 content decreased 0.16 days (4 h) after a damaging insult with barium chloride. In parallel, the 3D model increased the expression of cytokines supporting skeletal muscle repair, such as IL-6, and 12 days after injury it was able to increase MyH1 levels even above pre-injury levels. Furthermore, we tested and confirmed the effects of individual donors on the properties of our 3D model of skeletal muscle and showed that it is a suitable tool to study the interactions between different cell types. The model presented in this study shows clear advantages over similar 3D models, as it allows the replication of skeletal muscle biological processes in vitro without the complexity of advanced equipment or materials. The model responds to stimulation with external factors, appears to resemble the donor phenotype, can be used to study cell-to-cell interactions, and shows the expected response to biological processes such as muscle injury and hormonal treatment in vitro.